2018
DOI: 10.1016/j.eurpsy.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation treatment outcomes among people with and without mental and substance use disorders: An observational real-world study

Abstract: The inclusion of individuals with and without MSUD in the same protocol, allowing for individuals with MSUD undergoing their psychiatric treatment, generates at least comparable success rates between the groups. Predictors of treatment success were similar to those found in the general population. Facilities that treat patients with MSUD should treat tobacco use in order to reduce the disparities in morbidity and mortality experienced by this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 37 publications
0
24
0
13
Order By: Relevance
“…Another important topic is the reduction of smoking, which is frequent in patients with severe mental disorders ( 72 74 ). The reduction in smoking habit is not the primary outcome of the study, and for this reason we did not propose to patients specific pharmacological (e.g., nicotine patches, nicotine gum, bupropion, or nortriptyline) or non-pharmacological strategies (e.g., cognitive-behavioral therapy group targeted on substance abuse) for supporting smoking cessations, as already done in previous studies ( 26 ). Nevertheless, we expect a reduction in the number of cigarettes smoked per day, as a consequence of the global lifestyle improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important topic is the reduction of smoking, which is frequent in patients with severe mental disorders ( 72 74 ). The reduction in smoking habit is not the primary outcome of the study, and for this reason we did not propose to patients specific pharmacological (e.g., nicotine patches, nicotine gum, bupropion, or nortriptyline) or non-pharmacological strategies (e.g., cognitive-behavioral therapy group targeted on substance abuse) for supporting smoking cessations, as already done in previous studies ( 26 ). Nevertheless, we expect a reduction in the number of cigarettes smoked per day, as a consequence of the global lifestyle improvement.…”
Section: Discussionmentioning
confidence: 99%
“…On these premises, several psychosocial interventions—including behavioral, educational, and psychological components—have been developed worldwide for addressing these needs ( 20 25 ). In particular, some interventions have been specifically focused on improving dietary patterns [e.g., ( 24 )] or smoking habits [e.g., ( 26 )] or on physical inactivity, unhealthy dietary habits, and smoking [e.g., ( 22 , 23 )]. These lifestyle psychosocial interventions—that are different in format, setting, duration, and involved professionals—have been found to be effective in improving patients' physical health.…”
Section: Introductionmentioning
confidence: 99%
“…We did not have information on smoking or smoking cessation interventions, but it is possible that high rates of smoking contributed to the excess mortality in patients with SMI. Smoking cessation interventions are effective and well tolerated in patients with SMI [34][35][36], and they should be an integral component of lung cancer treatment.…”
Section: Overview Of Main Findingsmentioning
confidence: 99%
“…However, an RCT evaluating the efficacy of initiating smoking cessation treatment in patients admitted to a psychiatry ward has reported promising results 154 , as has an observational study on depressive smokers that used routinely collected data from a smoking cessation clinic in the Czech Republic and showed quit-rates of 25-33%, depending on the severity of depression when entering into the SCI, as well as improvements in the depression level in abstinent patients 155 . In addition, a recent real-world study on clinical practice showed no significant difference in abstinence rates between smokers with or without a mental disorder at the end of the 6-week treatment 156 . Unfortunately, the study only included a short-term followup, and, therefore, it is not possible to determine whether the results would be maintained in the long term 156 .…”
Section: Vulnerable and Disadvantaged Groupsmentioning
confidence: 95%
“…In addition, a recent real-world study on clinical practice showed no significant difference in abstinence rates between smokers with or without a mental disorder at the end of the 6-week treatment 156 . Unfortunately, the study only included a short-term followup, and, therefore, it is not possible to determine whether the results would be maintained in the long term 156 .…”
Section: Vulnerable and Disadvantaged Groupsmentioning
confidence: 95%